(untitled) (Indian Journal of Arid Horticulture, 2025)
Sugar apple cultivar ‘Balanagar’ comes to harvest during August-September under mild tropical climate, which coincides with monsoon rains resulting in poor fruit quality and high susceptibility to anthracnose and fruit fly. An attempt was made to advance the fruiting in this cultivar through hand defoliation in 2017-18 at ICAR IIHR, Bengaluru. The effects of defoliation on flowering and fruiting were compared. Early sprouting, flowering and fruit harvest were recorded in the defoliated trees. Earliest fruits were harvested during 3rd week of April (216 days) from the defoliated trees while the un-defoliated trees come to harvest during the 1st week of August (313 days) (P=0.01). Fruits with higher pulp per cent (61.6) and lesser seeds (31) were harvested from the defoliated trees (P=0.05). Defoliation did not affect the fruit weight and acidity significantly. Comparatively, higher yield per tree and fruit TSS (7.2 kg; 24.7°B) were recorded for the un-defoliated trees over the defoliated trees (6.8 kg; 23.1°B) (P=0.05). Results revealed that fruiting could be advanced by three months to April from the normal season of August-September with comparable fruit quality by defoliating the trees during 3rd week of September.